Research on the thermo-elastic deformation and fracture mechanism of the slipper retainer in the axial piston pumps and motors. (June 2019) - Haidak, Gaston; Wang, Dongyun; E, Shiju
Abstract: This article is based on the study of the thermo-elastic deformation and fracture mechanism of the slipper retainer which is revealed by its deformation and fracture. For this, the study of the kinematics around the retained slipper is made. An analytical study based on the formulation of the heat diffusion equations in the retainer, the strain and the elastic deformation and the friction forces between the retainer and the slipper is made. Subsequently, the simulation of the temperature and pressure distribution, strain and elastic deformation is performed; and these results clearly show the areas most exposed to breakage and destruction of the retainer. The whole pump is tested then was disassembled to observe, verify and analyse the state of the slipper retainer the simulation results in the laboratory. Solutions such as the quality of the material and the dimensions are proposed to improve the durability of the retainer. Highlights: The new mathematical model describing the simulation of the temperature and pressure distribution, strain and elastic deformation is performed. FEM performing the simulation of pressure, strain, elastic deformation and temperature. A test rig is designed to verify the proposed thermo-elastic deformation of the retainer. Solutions such as the quality of the material and the dimensions are proposed to improve the durability of the retainer.